1995
DOI: 10.4049/jimmunol.154.1.180
|View full text |Cite
|
Sign up to set email alerts
|

Multiple defects in innate and adaptive immunologic function in NOD/LtSz-scid mice.

Abstract: The scid mutation was backcrossed ten generations onto the NOD/Lt strain background, resulting in an immunodeficient stock (NOD/LtSz-scid/scid) with multiple defects in adaptive as well as nonadaptive immunologic function. NOD/LtSz-scid/scid mice lack functional lymphoid cells and show little or no serum Ig with age. Although NOD/(Lt-)+/+ mice develop T cell-mediated autoimmune, insulin-dependent diabetes mellitus, NOD/LtSz-scid/scid mice are both insulitis- and diabetes-free throughout life. However, because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,042 publications
(60 citation statements)
references
References 41 publications
1
59
0
Order By: Relevance
“…The observation is consistent with the well‐documented lack of adaptive immune cells, impaired innate immune cell subsets (e.g., macrophages) and a lack of a functional complement system which affects the activation of neutrophils in these mice. 66 , 67 , 68 , 69 We expanded upon these results by quantifying Cy5‐HA cryogel degradation in gp91 phox− mice, which are on the B6 background, but gp91 phox− neutrophils in affected hemizygous male mice lack superoxide production. 29 , 30 The functional deficiency of neutrophils in gp91 phox− is similar to the clinical observations of defective respiratory burst and phagocytosis affecting neutrophils in chronic granulomatous disease, in which there are normal neutrophil counts but impaired oxidative killing.…”
Section: Discussionmentioning
confidence: 99%
“…The observation is consistent with the well‐documented lack of adaptive immune cells, impaired innate immune cell subsets (e.g., macrophages) and a lack of a functional complement system which affects the activation of neutrophils in these mice. 66 , 67 , 68 , 69 We expanded upon these results by quantifying Cy5‐HA cryogel degradation in gp91 phox− mice, which are on the B6 background, but gp91 phox− neutrophils in affected hemizygous male mice lack superoxide production. 29 , 30 The functional deficiency of neutrophils in gp91 phox− is similar to the clinical observations of defective respiratory burst and phagocytosis affecting neutrophils in chronic granulomatous disease, in which there are normal neutrophil counts but impaired oxidative killing.…”
Section: Discussionmentioning
confidence: 99%
“…Backcrossing the Prkdc scid mutation onto various inbred strains revealed that non-obese diabetic (NOD).Prkdc scid mice support higher levels of human PBMC engraftment than any other strain tested [29]. This is largely due to NOD mice having impaired development and function of macrophages, natural killer (NK), NKT cells, and regulatory T cells (although not relevant for mice homozygous for Prkdc scid ) [30][31][32][33][34][35]. Immune cell defects in the NOD strain have largely been mapped to two loci designated insulin-dependent diabetes susceptibility 3 (Idd3) and Idd5, which contain genes encoding interleukin-2 (Il2), Il21, and Ctla4 (as reviewed in [36]).…”
Section: Development and Characterization Of Immunodeficient Strainsmentioning
confidence: 99%
“…NOD.Cg- Prkdc scid Il2rg tm1Wjl /SzJ (NSG) mice have profound defects in both innate and adaptive and immune responses 12 including: (1) loss of both T and B cell function 13 , (2) macrophages, NK cells and dendritic cells are found in NSG mice but are functionally compromised, (3) defects in the complement cascade 14 , 15 , (4) eosinophils are found in the bone marrow of NSG mice but not in the peripheral blood 16 and (5) monocytes and neutrophils are present in NSG mice although their functional capacity is unknown 15 . It was hypothesized that the absence of a functional innate and adaptive immune response would enhance the susceptibility of these mice to infection with nematode parasites, as opposed to the immunocompetent mice which were resistant to the infections.…”
Section: Introductionmentioning
confidence: 99%